(3LQ GdPjd aj Yde GdNjds - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdfgGQ hGddjd gPG cJGH CdaJg ai aVd GdNjd YRjR dWja ai HGHg hLjR SejJg LQ GdPjd ai Yde GdNjd PcQ Hg Ndb GdNjd s
(3BNQgG (B:s
(3hPGQY GSe GdcdH GdOjde PcQ GdOQGL bdJ RGO ai GdbGehS hVQH ef GdbWG Ojc GdLf aVd GdOjc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B582s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs